The Effect of Green Accounting implementation on Corporate Value of Mining Companies Listed in Indonesia Stock Exchange - I G. A. M. Asri Dwija Putri; Ni Putu Sri Harta Mimba; Ida Ayu Artha Widya Sari (AIBPM Publisher, 2019)
The implementation of Green Accounting needs to be disclosed by the company because information about the impact of the activities of the company will affect the value of the company. In this study, Green Accounting is provided by Environmental Performance and Environmental Disclosure. This study aims to determine the effect of Environmental Performance and Environmental Disclosure on corporate value. The object of this research is mining companies listed in Indonesia Stock Exchange in the period of 2013-2017. The number of observations obtained was as many as 35 observations using the non-probability sampling method specifically purposive sampling. The technical data analysis used is multiple regression analysis. Based on the results of the study, it shows that Environmental Performance does not have a positive effect on corporate value. However, Environmental Disclosure has a positive and significant effect on corporate value. The implication of this research theoretically supports stakeholder and legitimacy theory, while practically this research can provide good insight for investors and companies.